PEMULIHAN AIR TANAH BERDASARKAN KAJIAN HIDROGEOLOGI DI CEKUNGAN AIR TANAH BANDUNG - SOREANG - Dadi Harnandi (JURNAL SUMBER DAYA AIR, 2009)
The rapid development of many sectors at the Bandung-Soreang Groundwater Basin has increased thedemand for clean water. It is estimated that approximately 70 per cent of the clean water demand is stillfulfilled by ground water. In the last five years, the use of ground water from deep and dug wells has shown atendency of increase. In 2001, total use of groundwater reached 46.6 million cu m, and in 2005 had increasedto 51.4 million cu m. The increasing use of ground water at middle aquifer and deep aquifer has intensified thedepth of ground water level. A distribution of ground water level decrease at middle aquifer was observed atsome areas in West Java, i.e. South Cimahi 91.0 m bgl; Dayeuhkolot 62.0 m bgl; Rancaekek Cimanggung 68.0 m bgl; Majalaya 43.0 m bgl; and the city of Bandung 62.9 m bgl. The depth of groundwater at deep aquifers at areas such as, South Cimahi, Dayeuhkolot, Cikeruh and Rancaekek varied between24.7 - 68.2 m bgl. Between the years of 2000 and 2006, at middle- and deep aquifer respectively, the decreaseof ground water level showed a rate of 0.11 12.03 m/year and 0.16 2.61 m/year.